2022
DOI: 10.1002/ejoc.202200591
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Stereoselective Synthesis of Ynenamides through Gold(I)‐Catalyzed Hydroalkynylation of Ynamides

Abstract: Transition metal catalysis is a useful tool for C−C bond‐forming reactions. Of special interest is the hydroalkynylation reaction of alkynes, which provides a simple method for the synthesis of enynes representing interesting structural motifs in organic chemistry. So far, there are only a few examples of gold(I)‐catalyzed hydroalkynylation reactions. Herein, we were able to show experimentally that the gold(I)‐catalyzed hydroalkynylation of ynamides leads regio‐ and stereoselectively to the corresponding ynen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Recently, Haberhauer and co-workers found that the stereoselectivity for hydroalkynylation of oxazolidinone-derived ynamides could be altered to anti -adducts when a bulky cationic gold catalyst JohnphosAuSbF 6 (DAC) was employed (Scheme 15). 41 A gold acetylide complex, pre-synthesized with phenylacetylene and DAC, was demonstrated to be a better catalyst for hydroalkynylation of oxazolidinone-derived ynamides. Based on this fact, it is believed that the terminal alkyne first reacts with the cationic gold complex to deliver the active catalyst gold acetylide intermediate Int-25 .…”
Section: C–c Bond Formationmentioning
confidence: 99%
“…Recently, Haberhauer and co-workers found that the stereoselectivity for hydroalkynylation of oxazolidinone-derived ynamides could be altered to anti -adducts when a bulky cationic gold catalyst JohnphosAuSbF 6 (DAC) was employed (Scheme 15). 41 A gold acetylide complex, pre-synthesized with phenylacetylene and DAC, was demonstrated to be a better catalyst for hydroalkynylation of oxazolidinone-derived ynamides. Based on this fact, it is believed that the terminal alkyne first reacts with the cationic gold complex to deliver the active catalyst gold acetylide intermediate Int-25 .…”
Section: C–c Bond Formationmentioning
confidence: 99%